TRAINING OF TRAINER ANTI PRUNDUNGAN: PELAYANAN TERPADU PENCEGAHAN DAN PENANGANAN BULLYING DI LINGKUNGAN PONDOK PESANTREN MELALUI OFFICIAL HOSPITAL RUMAH SAKIT BHAYANGKARA, NUSA TENGGARA BARAT - Adiwibawa, Danang Nur; Anulus, Ayu; Purnamasari, Putu Prida (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
Bullying is a serious problem in educational environments, including Islamic boarding schools, which can affect children's physical and mental health. This community service program is a socialization of integrated services for the prevention and handling of bullying in a number of Islamic boarding schools in the NTB region, one of which is the NWDI Nabi Nubu Kekait Islamic Boarding School, Gunungsari, West Lombok, West Nusa Tenggara. This activity aims to provide education and integrated services to students, teachers, and related parties in Islamic boarding schools to increase awareness and ability to prevent and handle bullying cases effectively. The methods used are training, socialization, filling out questionnaires (bullying questionnaires in schools), and discussions. The results show that participants are active and understand about increasing awareness and ability to prevent bullying. The conclusion is that this socialization is something that needs to be held routinely so that every student and teacher in Islamic boarding schools can be more aware of the potential for bullying.